2019
DOI: 10.1002/pld3.117
|View full text |Cite
|
Sign up to set email alerts
|

Two members of the DUF579 family are responsible for arabinogalactan methylation in Arabidopsis

Abstract: All members of the DUF579 family characterized so far have been described to affect the integrity of the hemicellulosic cell wall component xylan: GXMs are glucuronoxylan methyltransferases catalyzing 4‐O–methylation of glucuronic acid on xylan; IRX15 and IRX15L, although their enzymatic activity is unknown, are required for xylan biosynthesis and/or xylan deposition. Here we show that the DUF579 family members, AGM1 and AGM2, are required for 4‐O–methylation of glucuronic acid of a different plant cell wall c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 16 publications
1
35
0
Order By: Relevance
“…The AGspecific glycosyltransferases (GTs) characterized include eight galactosyltransferases (GalTs; GALT2 to -6 and HPGT1 to -3) that transfer galactose onto Hyp (Basu et al, 2013(Basu et al, , 2015Ogawa-Ohnishi and Matsubayashi, 2015), two GalTs (GALT31A and GALT29A) involved in the synthesis of b-(1→6)-galactan side chains (Geshi et al, 2013;, two backbone b-(1→3)-Gal transferases (UPEX1 and GhGalT1; Qin et al, 2017;Suzuki et al, 2017), and two L-fucosyltransferases (FUT4 and FUT6;Liang et al, 2013;Tryfona et al, 2014). Recently, the terminal GlcA was described to be methylated by two 4-O-methyltransferases (AGM1 and AGM2) of the DUF579 family (Temple et al, 2019). Together, these enzymes are likely responsible for the glycosylation of a large number of proteins encoded in the Arabidopsis genome (Borner et al, 2003;Showalter et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The AGspecific glycosyltransferases (GTs) characterized include eight galactosyltransferases (GalTs; GALT2 to -6 and HPGT1 to -3) that transfer galactose onto Hyp (Basu et al, 2013(Basu et al, , 2015Ogawa-Ohnishi and Matsubayashi, 2015), two GalTs (GALT31A and GALT29A) involved in the synthesis of b-(1→6)-galactan side chains (Geshi et al, 2013;, two backbone b-(1→3)-Gal transferases (UPEX1 and GhGalT1; Qin et al, 2017;Suzuki et al, 2017), and two L-fucosyltransferases (FUT4 and FUT6;Liang et al, 2013;Tryfona et al, 2014). Recently, the terminal GlcA was described to be methylated by two 4-O-methyltransferases (AGM1 and AGM2) of the DUF579 family (Temple et al, 2019). Together, these enzymes are likely responsible for the glycosylation of a large number of proteins encoded in the Arabidopsis genome (Borner et al, 2003;Showalter et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Prior work has suggested that Arabidopsis DUF579 enzymes catalyze the methylation of GlcA sidechains present on GX and AGP. 2,16 In vitro biochemical evidence for xylan methyltransferase activity has previously been demonstrated for members of clade I in Arabidopsis. However, the analysis of these enzymes and their resultant structures is complicated by the redundancy of paralogous enzymes in many plant tissues, as well as a lack of robust analytical methods to isolate, detect, and quantify methyletherified structures in complex mixtures of cell wall carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
“…1 Recent reports suggest that members of DUF579 clade III catalyze 4-O-methylation of the β-GlcA residues present in the sidechains of Arabidopsis AGPs. 16,19 Taken together, these findings suggest that DUF579 enzymes act on a diverse set of saccharide targets and contribute to the synthesis of some of the most recalcitrant and least understood structures present in the plant cell wall. The discovery of the function of many enzymes from this family, together with analysis of mutants that lack these enzymes, presents a unique opportunity to further understand how nonglycosyl modifications influence plant cell wall architecture and function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown in tobacco protoplasts using a GFP-tagged pectin methylesterase inhibitor protein and its mutant without a GPI-anchoring signal that the late transport pathways of these proteins are different (De Caroli et al, 2011). The DUF576 family methyltransferases that act against AGP glycan have been detected not only in the Golgi apparatus but also in small punctate structures that are distinct from the Golgi apparatus (Temple et al, 2019). Similarly, a subset of glycosyltransferases involved in AGP glycan biogenesis was found in a non-Golgi punctate structure with an exocyst protein Exo70 homolog 2, which is a marker for exocyst-positive organelles, but not with a SNARE protein SYP61, which is localized in the trans-Golgi network (TGN) and subsequent secretory vesicles (Poulsen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%